A Systematic Review Analysis for Mobile Botnet Detection using GPS Exploitation - Yusof, M.; Madihah Mohd Saudi; Farida Hazwani Mohd Ridzuan (Universiti Sains Islam Malaysia, 2024)
At present, mobile botnet has become a cyber threat for smartphone users especially on the Android platform. It has the capabilities to exploit the vulnerabilities and steal confidential information in the victim's smartphone. Zeus, DroidDream and MisoSMS are examples of mobile botnets that have affected thousands of users worldwide. Therefore, this research paper presents a systematic review analysis on the existing techniques for mobile botnet detection techniques.It discusses the strengths and the weaknesses of the existing mobile botnet detection techniques and related works of mobile botnet that exploit GPS. This research paper can be used as a reference and guidance for those with the same interest.